2017
DOI: 10.1099/mgen.0.000110
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, virulence, and antimicrobial resistance of the KPC-producing Klebsiella pneumoniae ST307 clone

Abstract: The global spread of Klebsiella pneumoniae producing Klebsiella pneumoniae carbapenemase (KPC) has been mainly associated with the dissemination of high-risk clones. In the last decade, hospital outbreaks involving KPC-producing K. pneumoniae have been predominantly attributed to isolates belonging to clonal group (CG) 258. However, results of recent epidemiological analysis indicate that KPC-producing sequence type (ST) 307, is emerging in different parts of the world and is a candidate to become a prevalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
176
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(198 citation statements)
references
References 50 publications
15
176
1
6
Order By: Relevance
“…Complementing the increasing reports in the literature, our analyses reveal that ST307 is a highly successful MDR clone that shares many traits with ST258, but is closely associated with bla CTX--M--15 rather than bla KPCs . With sufficient exposure ST307 can acquire and disseminate carbapenemases [1][2][3], and likely other clinically important AMR determinants. ST307 appears to be readily transferred between countries and has already become globally disseminated, yet has remained largely unnoticed for almost 20 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementing the increasing reports in the literature, our analyses reveal that ST307 is a highly successful MDR clone that shares many traits with ST258, but is closely associated with bla CTX--M--15 rather than bla KPCs . With sufficient exposure ST307 can acquire and disseminate carbapenemases [1][2][3], and likely other clinically important AMR determinants. ST307 appears to be readily transferred between countries and has already become globally disseminated, yet has remained largely unnoticed for almost 20 years.…”
Section: Resultsmentioning
confidence: 99%
“…For the majority of genomes carrying bla CTX--M--15 (n=88/89) BLASTn confirmed that this gene was located downstream of ISEcp1, which forms a transposon to mobilise bla CTX--M--15 and promotes its expression [23]. Four complete ST307 IncFII K /IncFIB K bla CTX--M--15 plasmids have been published [2], and share an insertion of the ISEcp1/bla CTX--M--15 transposon within Tn3. Read--mapping to pKPN3--307_typeA (accession KY271404) and assembly graph inspections of our bla CTX--M--15 --positive genomes showed that all carried the same ISEcp1/bla CTX--M--15 transposon.…”
Section: St307 Virulence and Antimicrobial Resistance Genesmentioning
confidence: 94%
See 1 more Smart Citation
“…The ST29 and ST323 MDR isolates each 9 harboured 4-6 plasmids (Table S3). Notably, all the acquired AMR genes in these genomes were localized to the same >200 kbp FIB K /FII K plasmid backbone encoded conjugative transfer functions and shared close similarity (>90% coverage and 99% identity) with plasmid pKPN3-307_type A from an Italian K. pneumoniae [21]. However there were some differences in the MDR regions, resulting in different susceptibility profiles ( Figure S2).…”
Section: Mdr Mechanisms and Transmissionmentioning
confidence: 99%
“…A reference bla KPC plasmid sequence database composed of bla KPC -harbouring contigs/plasmids from long-read sequencing of isolates in this study and all complete bla KPC plasmids from (42-44) (August 2018) was used for bla KPC plasmid typing within this study. To construct this database, all 279/6018 evaluable plasmid sequences carrying bla KPC were first compared using dnadiff (45) to obtain the pairwise similarity between any two plasmid sequences p i and p j .…”
Section: Methodsmentioning
confidence: 99%